Abundance and ecological classification of fish Species: A case study of Owalla Reservoir, Osun State, Nigeria - Adams Ovie Iyiola; Yetunde Folasade Taiwo; Berchie Asiedu (Ruhuna Journal of Science, 2022)
Globally, we are experiencing higher species extinction rates than ever before which can critically affect food and nutrition security. The ecological classification of fish species was assessed in Owalla reservoir, Okinni, Osun State, Nigeria. Fish landings of fishermen were sampled for 12 months from September 2019 to August 2020). The species were identified and grouped into herbivores, carnivores, and omnivores, and the fish abundance was recorded. The Forage-Carnivore ratio (F/C ratio) was calculated to express the ecological structure of the reservoir. A total of 15 fish species (n=1035 fish) were identified. In the dry and wet seasons, 15 species (692 fish) and 11 species (343 fish) were recorded, respectively, and herbivores were more abundant than carnivores. Chrysichthys nigrodigitatus (25.9%) was the most abundant species and Cichlidae (55.5%) was the most abundant family. The overall F/C ratio during the combined, dry and wet seasons were 1.35, 1.01 and 2.57, respectively. The ecological structure as indicated by the F/C ratio was unbalanced, but in the wet season, it was close to being balanced. We proposed management measures such as fishing across the trophic levels, efficient monitoring and surveillance, regulation of mesh sizes, and registration of fishermen in addition to routine data collection.